Analisis Keamanan Media Sosial Pada PT. RN - Husnul Khatimah; Christian Wiradendi Wolor; Eka Dewi Utari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Social media has become an important tool in a company's communications and marketing strategy, but its use also carries various security risks that can have a serious impact on a business's reputation and operations. This research aims to analyze security aspects in the use of social media by companies, focusing on potential threats such as data leaks, cyber attacks, the spread of false information, and misuse of official accounts. The methods used include literature studies, observations of security practices in several companies, and analysis of implemented social media security policies.